"A Kind of Hamlet": Rescripting Shakespeare and the Refusal of Racial Scripts in James Ijames's Fat Ham. - Corredera, Vanessa I. (Humanities (2076-0787), 2025)
In his 1926 "Criteria of Negro Art," W.E.B. Du Bois advocates for art's role in the quest for liberation while acknowledging the challenges facing the creation of Black art, observing, "We can go on the stage; we can be just as funny as white Americans wish us to be; we can play all the sordid parts that America likes to assign to Negroes; but for anything else there is still small place for us." He elaborates, "As it is now we are handing everything over to a white jury." Almost 100 years later, the issues Du Bois raises about Black art, the quest for Black freedom, and the structures of white supremacy that stymie this striving remain troublingly relevant for contemporary Shakespearean performance. As scholars have noted, complex challenges (the Shakespeare system, capitalist pressures, etc.) continue to make contemporary American Theater, and Shakespeare within it, "still a small space" for Black artists. In the face of these forces, what can and does resistance look like for Black artists within predominantly white theatrical spaces? Here, I tackle this question, thereby continuing the scholarly interrogation of the relationship between contemporary Shakespeare performance, race, and social justice. I turn to a recent lauded adaptation of Shakespeare that, in its move from local theater to Broadway, inevitably had to engage with the structures of American theater's (and Shakespeare's) racial capitalism—James Ijames's Pulitzer-prize-winning Fat Ham (2021). Fat Ham, I contend, tackles head on the historical racial scripts imposed on Black subjects and, through a range of adaptive moves, exposes and resists them, offering counterscripts that insist on the personal and interpersonal complexity and flourishing of Black subjectivity.